A constant shear stress strategy for establishing in situ viscosity models of photoinduced polymerization of acrylamide. Issue 15 (16th June 2021) - Sun, Guangdong; Huang, Yi; Lv, Lingling; Li, Dapeng; Fan, Qinguo; Li, Yongqiang; Shao, Jianzhong
Abstract: In situ viscosity kinetics models for blue light induced radical polymerization of acrylamide (AM) were proposed and established with camphorquinone/4‐(dimethylamino)‐2‐ethylbenzoate/diphenyl iodonium hexafluorophosphateas the photoinitiators. In order to minimize the impact of shear effect on polymer network, a constant shear stress technique of photo‐rheometry was proposed to characterize in‐situ viscosity behavior of acrylamide solution during the photopolymerization. The effect of various factors, for example, the dosages of initiator, monomer, and light intensities, on viscosity, polymerization and gelation behavior of AM solution was systematically analyzed. The viscosity advancement behavior was shaped by the joint action of the movement, growth and entanglement of molecular chains, and shear orientation. Different power‐law kinetic models were found in three curves, time‐related viscosity, shear rate‐related viscosity and time‐related shear rate. Such school of thought on constructing the viscosity advancement model provides a new theory and method of systematical studying on the photorheological theories. Furthermore, a trinitarian theoretical model that represented the access from the microscopic kinetics of free radical polymerization to the movement behavior of polymer chains was successfully established by mapping the photoinduced viscosity kinetics model onto the polymerization and crosslinking kinetics model. Abstract :